(untitled) (Raparin Journal of Humanities (RJH), 2024)
This study is entitled "Intertextual Context in Kurdish Political Discourse, with Reference to Referendum Discourse". Intertextual context is Norman Fairclough’s perspective in critical discourse analysis which is concerned with explaining the sources of discourse production. It highlights what these sources are and where they relate to other texts. This subject is at the second level of critical discourse analysis which is known as discourse interpretation level. It is a significant part which aims at reaching the common knowledge sources of discourse participants via interpreting the intertextual context of a given discourse. The aim is to achieve a common interpretation, for, in this regard; any discourse or linguistic act is in a deep relationship with some other texts. The current study is an attempt to interpret and to a large extent identify the sources of the referendum discourse (the whole face to face speeches of Massoud Barzani, Chairman of the High Council for Referendum). This study employs the descriptive analysis method. It, first, presents Fairclough’s view on intertextual context. Then, the depicted examples of this are presented in the referendum discourse.